Des normes professionnelles auto-prescrites. Le cas de la mise en œuvre de la démarche d’enseignement scientifique en Suisse romande - Corinne Marlot; Catherine Audrin; Ludovic Morge (Recherches en Éducation)
This research hypothesizes a relationship between the difficulties for teachers of implementing the inquiry based science education (IBSE) in the classroom and the existence of professional standards. These standards described as self-prescribed, are the result of the actors' renormalization of primary requirements (programs) and secondary requirements (the discourses of training institutions). In this article, we report on the exploratory phase of this research linked to a questionnaire survey of primary school teachers, both beginners and experienced, in French-speaking Switzerland. Data processing was carried out using factor analysis and hierarchical bottom-up classification. This quantitative analysis revealed the following: (1) the existence of self-prescribed standards for the establishment of the inquiry based science education(2) the existence of 4 categories of teachers according to their adherence to the pedagogical and epistemological standards of the IBSE; (3) hypotheses concerning the existence of a generational cleavage (experienced/non-experienced) and/or a cleavage linked to the level of education(students from 4 to 7 years old/students from 8 to 11 years old) that explains the variability in the rate of adherence to the epistemological and didactic norms of the IBSE.